Subsequent child protection contact for a cohort of children reported to child protection prenatally in one Australian jurisdiction. (13th January 2023) - Octoman, Olivia; Arney, Fiona; Meiksans, Jenna; Flaherty, Rosemaria; Chong, Alwin; Ward, Fiona; Taylor, Cathy
Abstract: Repeated reporting to child protection is common. One approach to early intervention is for jurisdictions to receive and respond to child protection concerns raised before children are born. Despite this, little research has comprehensively examined subsequent child protection contact for those first reported prenatally. This study aimed to examine the subsequent child protection contact for up to a two‐year period for a cohort of children who were reported about prebirth. Child protection administrative data were extracted for 640 children reported for a concern about an unborn child in a single jurisdiction during 2014. Data about child protection contacts included reports, investigations, substantiations and out‐of‐home placements for children reported prenatally. Of the 640 children, 79% reported about prenatally also had contact with child protection between birth and age two. From birth and up to age two, children reported prenatally had between zero and 21 reports. Twenty‐two per cent of the children reported prenatally were removed from their birth parents and placed in out‐of‐home care prior to age two. These findings highlight the importance of intervening and supporting families prior to and during pregnancy to reduce harm to children and reduce the need for contact with child protection.